2007
DOI: 10.1002/cne.21336
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of SDF‐1α and SDF‐1γ mRNAs, migration pathways, and phenotypes of CXCR4‐expressing neurons in the developing rat telencephalon

Abstract: Cortical GABAergic neurons originate in the ventral telencephalon, invade the cortex via tangential migration, and integrate into the cortical plate by surface-directed and ventricle-directed migration. In mice lacking CXCR4 or SDF-1, GABAergic neurons fail to complete their migration. It is presently unknown which parts of the migration of CXCR4-expressing GABAergic neurons are driven by SDF-1. Here we compared patterns of SDF-1 isoforms and CXCR4 in the developing rat telencephalon. In the ventral telencepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 53 publications
6
85
0
Order By: Relevance
“…Furthermore, the ventral-to-dorsal gradients within the cortical SVZ and cortical plate, may regulate their tangential dispersion. In contrast, as has been reported in detail by others (Stumm et al, 2003(Stumm et al, , 2007Tissir et al, 2004;Daniel et al, 2005), the Cxcl12 receptor Cxcr4 is weakly expressed in the migrating interneurons entering the cortex at both E13.5 and E16.5 [supplemental The distribution pattern of Cxcl12 in the meninges and SVZ suggests that it may play a role in organizing interneurons into streams, whereas the tapering pattern of Cxcl12 in the SVZ may facilitate the lateralto-medial dispersion of interneuron. Moreover, the spatial gradient (high in meninges to low in SVZ) and the temporal gradient (low at E13.5 to high at E16.5) of Cxcl12 suggest it may play a critical role in the MZ accumulation of interneurons in that particular time window.…”
Section: Spatial and Temporal Regulation Of Cxcl12 And Cxcr4 Expressimentioning
confidence: 56%
See 1 more Smart Citation
“…Furthermore, the ventral-to-dorsal gradients within the cortical SVZ and cortical plate, may regulate their tangential dispersion. In contrast, as has been reported in detail by others (Stumm et al, 2003(Stumm et al, , 2007Tissir et al, 2004;Daniel et al, 2005), the Cxcl12 receptor Cxcr4 is weakly expressed in the migrating interneurons entering the cortex at both E13.5 and E16.5 [supplemental The distribution pattern of Cxcl12 in the meninges and SVZ suggests that it may play a role in organizing interneurons into streams, whereas the tapering pattern of Cxcl12 in the SVZ may facilitate the lateralto-medial dispersion of interneuron. Moreover, the spatial gradient (high in meninges to low in SVZ) and the temporal gradient (low at E13.5 to high at E16.5) of Cxcl12 suggest it may play a critical role in the MZ accumulation of interneurons in that particular time window.…”
Section: Spatial and Temporal Regulation Of Cxcl12 And Cxcr4 Expressimentioning
confidence: 56%
“…1, available at www.jneurosci.org as supplemental material). Because Cxcl12 continues to be expressed in the meninges during that time window (Stumm et al, 2003(Stumm et al, , 2007, it raises the issue of how the GFPϩ cells adjust their responsiveness to Cxcl12 during this period; either the GFPϩ cells change their responsiveness (losing their attractive response or becoming repulsed by Cxcl12), or the cues that drive the radial migration are dominant over Cxcl12. To address this, we examined Cxcl12 responsiveness during this time period by placing Cxcl12-soaked beads into the cortical plate of P0 cultured slices.…”
Section: Cxcl12 Is Only a Chemoattractant For Lhx6-gfp؉ Interneurons mentioning
confidence: 99%
“…Certain chemokines, such as CXCL12 and CXCL1, are induced during CNS development and coordinate the proliferation, migration, and differentiation of neural precursor cells (NPCs) (Stumm et al 2007;Tsai et al 2002), which suggests they might also participate in CNS regenerative processes. In this way, Patel et al (2010) demonstrated that CXCR4 (the receptor of CXCL12) activation is important for the remyelination of the CPZ-demyelinated mouse by induction of OPC differentiation.…”
Section: Underlying Mechanisms In Demyelination/ Remyelination Processesmentioning
confidence: 99%
“…Recently, it has been reported that CXCL12, a member of the CXC subfamily of chemokines [also known as SDF-1 (stromal cell-derived factor-1)], is expressed in the meninges and in the SVZ of the developing cortex in a pattern that is consistent with a role for this molecule in the intracortical guidance of GABAergic interneurons (Stumm et al, 2003;Tiveron et al, 2006;Stumm et al, 2007). However, to what extent this signaling system is directly required for the migration of interneurons within the cortex and how this process may influence their final distribution in the cortex remains to be elucidated.…”
Section: Introductionmentioning
confidence: 95%